ENTITY AND MAINTENANCE OF THE MONITORING SYSTEM OF THE INDUSTRIAL ENTERPRISES (Publishing House of the State University of Management, 2018)
The relevant issues of implementation at the enterprises of the industry of system of monitoring of their production economic activity from the point of view of assessment and the forecast of changes of key performance indicators under the influence of external and internal factors have considered. It has proved that monitoring of development of the enterprise is an indicator of success of their activity and reflects degree of appeal to investors. By results of the conducted research, the authors of the article have created the main directions of monitoring of the enterprises for identification of industry leaders.